Platelet Activation in High D-Dimer Plasma Plays a Role in Acquired Resistance to Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors in Patients with Mutant Lung Adenocarcinoma - Lee, Meng-Jung; Weng, Chih-Ming; Chao, Wei; Fang, Yueh-Fu; Chung, Fu-Tsai; Lin, Chien-Huang; Kuo, Han-Pin (Frontiers in Oncology, 2022)
Objective: Platelet activation and adhesion to cancer cells increase release of multiple factors which contribute to EMT and chemo-resistance. Elevated levels of D-dimer have been associated with poor clinical outcomes in lung cancer. Platelets in high D-dimer plasma may be activated and implicated in acquired resistance to EGFR TKI in advanced lung adenocarcinoma with mutant EGFR. Materials and methods: Clinical responsive rate (RR), progression free survival (PFS) and overall survival (OS) were prospectively measured in treatment-naïve lung adenocarcinoma patients with activation mutation. Plasma or platelets from patients with high or low D-dimer level were obtained to investigate the cytotoxic effects of TKIs on mutant cancer cells, and the mechanistic pathways were also explored. Results: Patients with high D-dimer had worse RR, PFS and OS. High D-dimer plasma induced resistance to gefitinib, erlotinib, afatinib or osimertinib in EGFR mutant lung cancer cells. Depletion of platelets in high D-dimer plasma reversed the resistance to TKI. Platelets of high D-dimer plasma had higher adherence capacity to cancer cells, and induced EGFR and Akt activation as well as EMT through Src activation. Inhibition of platelets adherence or activation of Src or Akt conquered the resistance to TKI. The acquired resistance to TKI by high D-dimer plasma was less attributed to secondary gene mutation. Conclusion: Increased platelet activation in the high D-dimer plasma may contribute to 1st line acquired EGFR TKI resistance. Thus, therapeutic strategy against platelet activation in patients with high D-dimer levels may improve efficacy of 1st line treatment with EGFR TKI.